Hospital care for elderly COVID-19 patients - Jack Roberto Silva Fhon; Luipa Michele Silva; Zoila Esperanza Leitón-Espinoza; Fernanda de Brito Matiello; Jessica Silva de Araujo; Rosalina Aparecida Partezani Rodrigues (Universidade de São Paulo, 2020)
Objective: to analyze the newspaper articles on hospital care for elderly COVID-19 patients in online newspapers. Method: documentary, retrospective, descriptive and exploratory research. The data were collected from articles published on open-access websites of 12 newspapers from the following countries: Brazil, Spain, United States, France, Italy and Portugal. Results: out of 4,220 newspaper articles identified in this regard, 101 were selected after applying the inclusion criteria, the majority coming from Italy. The data analysis revealed three thematic categories: the care for patients with COVID-19 in the health system; the work process of the health team and its concern with contagion; and ethical dilemma in care for the elderly during hospitalization. Conclusion: the COVID-19 pandemic presented itself quickly and was widely reported in all countries. The health systems need to reorganize for care to the global population, especially the elderly, considering their weaknesses and also the lack of prior professional training to offer care to this population.